Impacts of alternative aviation fuels on engine cycle design and aircraft mission capability - Sasi, Sarath; Mourouzidis, Christos; Roumeliotis, Ioannis; Nikolaidis, Theoklis; Pachidis, Vassilios; Norman, Justin (American Society of Mechanical Engineers (ASME), 2023)
Recent 2050 net zero targets for aviation have sparked interest among the industry players to seek alternative aviation fuels as a pathway for the immediate alleviation of its carbon footprint. This paper aims to shed light on the opportunities and challenges that zero & low-carbon alternative fuels can provide from a technical standpoint. To address this aim, candidate fuels for aviation were selected from five broad classes of fuels. Then, a preliminary thermodynamic engine cycle design space exploration of a modern three spool turbofan is conducted to identify the fuel impact on cycle performance. Following that, an integrated Engine-Aircraft mission assessment for a Boeing 787 style aircraft with a three spool turbofan is conducted to assess performance at the mission level and explore opportunities and challenges for both powerplant and aircraft, accounting for fuel storage. Finally, an investigation of the opportunities available for the proposed fuels to be used as a heat sink is presented. The results indicate that zero-carbon fuels expand the design space for the powerplant cycle, allow for higher BPR, lower energy specific fuel consumption, lower peak cycle temperatures compared to the rest of the fuels, and provide significant cycle redesign opportunities. On a mission level, cryogenic fuels are penalized for block energy consumption due to the significant weight and size of the fuel storage system, while liquid alternative fuels are comparable to kerosene in terms of emissions and block energy consumption. Concerning Hydrogen, Methane, and Ammonia, the thermal power requirement for fuel conditioning (pressure and temperature rise) is calculated to be 2.2MW, 1.3MW, and 1MW respectively for a 240kN SLS thrust class engine during take-off.
Keywords: alternative aviation fuels; engine cycle design space; fuel conditioning; zero carbon fuels; Boeing 787